EXPLICIT OR IMPLIED ‘EASTERNISATION’: THE CASE OF SITUATIONAL FORCES IN SOCIAL PSYCHOLOGY - Yu, Ke (New Voices in Psychology, 2017)
Conventional West/East convergency theory tends to either emphasise the East’s westernising process, or confines discussion to the West’s adoption of Eastern cuisine, medicine and health practices. This article expands the discussion on the West’s easternisation. It elaborates on the increasing importance assigned to the situation in the West particularly in social psychology – a traditionally Western discipline adopting a seemingly eastern-oriented notion as its central focus. I demonstrate how the notion of situational forces has gained increasing acceptance in social psychology, how its popularity has spread to other disciplines such as philosophy and into general public discourse. I examine the origin of this evolvement (particularly whether it manifests any conscious appropriation of Eastern thought) by tracking the influences on its key figures. The findings suggest that this case of ‘easternisation’ does not result from a conscious uptake of Eastern philosophy, but rather seems to be a separate, independent development within the West. I propose that this may be a natural result of Western dualism and the tendency to swing between perceived opposites, as well as of the Western insistence on observation and empiricism as the primary sources of knowledge.